Keefektifan Model Creative Problem Solving terhadap Kemampuan Representasi Matematik Peserta didik pada Materi Fungsi - Dedi Setyawan; Hermanto Hermanto; Harliana Harliana (Jurnal Pendidikan dan Pembelajaran, 2022)
Mathematics is one of the subjects that aims to solve abstract problems that are changed to everyday problems. Based on the results of observations and interviews with mathematics teachers at SMP Negeri 4 Muncar, information was obtained that students' mathematical representation abilities were low, this was because teachers never connected mathematics material with everyday life. So the perception that mathematics is a difficult and scary subject takes root in students. Mathematical representation abilities can be developed using a learning model based on problem solving. Therefore, in this study, researchers used the Creative Problem Solving model as an effort to improve students' representational abilities.This research uses quantitative research, with a quasi-experimental design. The population in this study were all students of class VIII of SMP Negeri 4 Muncar, while the sample of this study was students of class VIII A and VIII D. The sample selection in this study was carried out using students' end-of-semester test scores, then tested for normality and homogeneity. Meanwhile, to determine the experimental class and control class, the researcher used random sampling technique. This study aims to measure the effect of the Creative Problem Solving model on students' representational abilities and to determine the differences in student learning outcomes on the representation of function material using the Creative Problem Solving model. Based on the hypothesis test, the value of sig. (2 tailed) < 0.000 <0.05 can be concluded that there is a significant influence between the Creative Problem Solving model and the representation ability of class VIII students of SMP Negeri 4 Muncar.